The Community Service Program: Education on Diabetes Mellitus Complications - Kusuma, Kristiana Wahyu; Mulyaningsih, Erika Agung; Rachmadhani, Yuannisa; Bestiantono, Firdaus Azzahra Ramadhani (Universitas Ahmad Dahlan, 2025)
Indonesia ranks fifth globally in diabetes cases, with 19.5 million sufferers in 2021, projected to reach 28.6 million by 2045. Diabetes Mellitus (DM) is a chronic disease with serious complications such as retinopathy, nephropathy, and cardiovascular disorders that lower quality of life. A key challenge is the low awareness of early complication signs among patients and families. This community service program, held on January 25–28, 2025, at Mojowarno Christian Hospital, aimed to improve the knowledge and empowerment of DM Club members through interactive education, simulations, and role-plays. Post-test results showed a 35% increase in knowledge, with 85% of participants able to identify complication signs. However, 15% still showed limited understanding, highlighting the need for more targeted education. This program demonstrates that structured community-based education can effectively improve diabetes literacy and management. Similar initiatives should be expanded to reduce the impact of DM complications nationwide.